2005
DOI: 10.1002/sce.20077
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of teaching physics to preservice elementary teachers: Orientations of the professor, teaching assistant, and students

Abstract: ABSTRACT:The purpose of this study was to understand how the professor, teaching assistant, and students experienced inquiry-based science instruction in an undergraduate physics course designed for elementary education majors. During the teaching of a 6-week electricity unit, the professor faced several challenges: knowing when and how to tell the scientifically accurate answer, deciding when and how to introduce scientific terminology, and doing inquiry vs. testing. The professor and the teaching assistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…It is known that teaching at the university level was essentially run didactically in contrast to the constructivist instructions. If learning through constructivist instructions is to be realized in today's schools, university physics and pedagogy courses must be run in such a way that STs could live through it [15]. But inconsistencies between teacher educators' discourses or expectations and their practices in our TEP and physics teachers tend to teach as they were taught [34] may cause STs to fail in the internalization of constructivist teaching [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that teaching at the university level was essentially run didactically in contrast to the constructivist instructions. If learning through constructivist instructions is to be realized in today's schools, university physics and pedagogy courses must be run in such a way that STs could live through it [15]. But inconsistencies between teacher educators' discourses or expectations and their practices in our TEP and physics teachers tend to teach as they were taught [34] may cause STs to fail in the internalization of constructivist teaching [32].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the orientations cover also the emotional and general school objectives and a teacher may have more than one orientation bearing the core and peripheral objectives in mind. But in literature a number of researchers (15)(16)(17) used these categories as a quick fix and they chose to report only the orientation they thought dominant even if participants held characteristics of multiple orientations [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These orientations utilize instructional characteristics that are always apparent and observable (p. 101) and are specific to science education. Friedrichsen and Dana (2005) and Volkmann, Abell, and Zgagacz (2005) provide a concise overview and help establish a level of construct validity of these science-teaching orientations.…”
Section: Methods Used To Explore the Two Continuamentioning
confidence: 99%
“…The review of literature also showed that a number of studies were conducted on the student teachers studying in the pre-service (Gitlin et al, 1999;Haefner, 2004;Joram, 2007;Newman et al, 2004;Richardson & Liang, 2008;Van der Linden et al, 2012) and elementary (Volkmann, Abell & Zgagacz, 2005) and secondary science teacher education programs (Crawford, Zembal-Saul, Munford, & Friedrichsen, 2005) and with the student teachers studying history (Pendry and Husbands, 2000), geography (Spronken-Smith et al, 2008), chemistry and biology (Sozbilir, 2007), and science (Demir & Abell, 2010).…”
Section: Inquiry In Teacher Educationmentioning
confidence: 99%